Methods for Determining Bilirubin Level in Neonatal Jaundice Screening and Monitoring: A Literature Review - Fahmi Akmal, Dzulkifli (Universiti Malaysia Perlis (UniMAP), 2019)
Link to publisher's homepage at http://jere.unimap.edu.my